Omaso-abomasal adenocarcinoma in a female Arabian camel (Camelus dromedarius). Issue 1 (1st January 2018) - Tharwat, Mohamed; El-Shafaey, El-Sayed; Sadan, Madeh; Ali, Ahmed; Al-Sobayil, Fahd; Al-Hawas, Abdullah
ABSTRACT: This report describes the case of a 15-year-old female Arabian camel with omaso-abomasal adenocarcinoma showing prolonged anorexia with colic bouts leading to cachexia during the last 6 months. Hematological and biochemical findings were indicative of a moderate to severe haemorrhagic anaemia. Ultrasonographic examination revealed hyperechoic severely thickened (68 mm) and corrugated omaso-abomasal walls with heterogonous contents. Exploratory laparotomy revealed a large barrel-shaped mass with dense contents including parts of the compound stomach adhered to the parietal peritoneum. A definitive diagnosis was based on histopathological examination confirming the mass as an omaso-abomasal adenocarcinoma. Omaso-abomasal adenocarcinoma should be included in the differential diagnosis of abdominal tumours in camel.